TESTING THE ACCURACY OF MEASURED VALUES IN CONTINUOUS LONG-TERM GEODETIC MONITORING - Jan Vaněček; Martin Štroner (Acta Polytechnica, 2016)
widespread used method. In this paper, an analysis of the accuracy and its changes over time of the measured values in continuous geodetic monitoring is presented. For the analysis, a set of data measured in the period of time between January 2006 to July 2010 was used. The main method of the analysis is a linear-harmonic function approximation.